City Building: the participation in the production of income in urban formation of Guaçuí-ES. - Mendonça, Marcos Cândido; Campos Júnior, Carlos Teixeira de (Geografares, 2016)
This article discusses the participation of real income in urban education Guaçuí municipality of Southwest State of Espírito Santo. The theoretical analysis assumed seize the city (its built space), articulated the productive space, so in general, necessary for the reproduction of capital in the city urban conditions, by which they showed in the set of investment strategies in urban activities the development prospect of gains for the valuation of real property. And this value is related to the capitalist use of land through the creation of urban conditions and construction of rental housing. The conclusion is that capital originated in the field also encountered in the construction of the city the opportunity to reproduce and thereby interfere with the spatial configuration of the city. Accordingly, we sought to understand the metamorphosis of wealth from the countryside to the city in Guaçuí, in which the value of urban real estate was the significance of reserve and allowed the obtaining of income. Considering the importance of the participation of the municipality Guaçuí the regional economy were significant transfers of surplus from the countryside to the city during the first half of the last century, enabling rentier show the interference of production (for the purpose of earning income through the use of property urban) land in the urban training town. Access to information, including probate proceedings on the initiatives of the business diversification of farmers and traders, helped identify initiatives such as the creation of urban infrastructure and services, as well as the construction of rental housing, allowing the valuation of real property and the transformation of the city Guaçuí.Keywords: Regional economy. Urban infrastructure. Urban services. Housing construction. Real estate.